Food security and sustainability: can one exist without the other?. Issue 13 (16th February 2015) - Berry, Elliot M; Dernini, Sandro; Burlingame, Barbara; Meybeck, Alexandre; Conforti, Piero
Abstract: Objective: To position the concept of sustainability within the context of food security. Design: An overview of the interrelationships between food security and sustainability based on a non-systematic literature review and informed discussions based principally on a quasi-historical approach from meetings and reports. Setting: International and global food security and nutrition. Results: The Rome Declaration on World Food Security in 1996 defined its three basic dimensions as: availability, accessibility and utilization, with a focus on nutritional well-being. It also stressed the importance of sustainable management of natural resources and the elimination of unsustainable patterns of food consumption and production. In 2009, at the World Summit on Food Security, the concept of stability/vulnerability was added as the short-term time indicator of the ability of food systems to withstand shocks, whether natural or man-made, as part of the Five Rome Principles for Sustainable Global Food Security. More recently, intergovernmental processes have emphasized the importance of sustainability to preserve the environment, natural resources and agro-ecosystems (and thus the overlying social system), as well as the importance of food security as part of sustainability and vice versa . Conclusions: Sustainability should be considered as part of the long-term time dimension in the assessment of food security. From such a perspective the concept of sustainable diets can play a key role as a goal and a way of maintaining nutritional well-being and health, while ensuring the sustainability for future food security. Without integrating sustainability as an explicit (fifth?) dimension of food security, today's policies and programmes could become the very cause of increased food insecurity in the future.